Anxiety Symptoms Questionnaire (ASQ): development and validation. Issue 6 (18th December 2019) - Baker, Amanda; Simon, Naomi; Keshaviah, Aparna; Farabaugh, Amy; Deckersbach, Thilo; Worthington, John J; Hoge, Elizabeth; Fava, Maurizio; Pollack, Mark P
Abstract : Background: The Anxiety Symptoms Questionnaire (ASQ) is a brief self-report questionnaire which measures frequency and intensity of symptoms and was developed to improve assessment of anxiety symptoms in a clinical setting. We examined the reliability and validity of the ASQ in patients with anxiety disorders and/or depression, non-clinical control subjects and college students. Methods: 240 outpatients with generalised anxiety disorder, social anxiety disorder, panic disorder or major depressive disorder were administered the ASQ and additional questionnaires measuring depression and anxiety, as were 111 non-clinical control subjects and 487 college students. Factor analysis, Pearson's correlation coefficients and logistic regression were used to assess reliability and validity. Test–retest reliability of the ASQ was measured using a subset who were re-administered the ASQ after 4 weeks. Results: Factor analysis revealed measurement of a single dimension by the ASQ. Internal consistency and test–retest reliability were strong. The ASQ total score also significantly distinguished patients with an anxiety disorder from the clinical controls above and beyond the clinician-rated Hamilton Anxiety Scale. Conclusions: The ASQ is a valid, reliable and effective self-rated measure of anxiety and may be a useful tool for screening and assessing anxiety symptoms in psychiatric as well as college settings.